Genetic distance within and between populations of Tiv and Fulani chicken ecotypes - Gambo, D.; Momoh, O. M.; Gwaza, D. S.; Addass, P. A. (Nigerian Journal of Animal Science and Technology (NJAST), 2019)
The study was conducted to determine genetic distance between chicken ecotypes using linear body measurements of birds from ten randomly selected localities. The localities were Uikpan, Daudu, Kadarko, Yelwata and Cohor for the Tiv ecotype and Lafia, Akurba, Adogi, Asakio and Namu for the Fulani ecotype. A total of 1,500 birds (750 males and 750 females) were used for the study. This comprised of one hundred and fifty birds (75 males and 75 females) from each of the selected localities. Data collected were body length, shank length, wing length, beak length and breast girth and subjected to stepwise discriminatory analysis and canonical discriminate analysis to assess the discriminatory power of each variable. Genetic distance between the ecotype was obtained using Mahalanobis D2 statistics of SPSS Statistical software with the aid of means of each discriminate variable. The results obtained showed that the genetic distances due to morphological characteristics within and between the two ecotypes were all significant. The summary of the classification results of location effect on the original and percent counts were 52.5% and 44.00% correctly classified based on location for the Tiv and the Fulani ecotypes, respectively. In addition, the classification results of ecotype effect on the original and percent counts were 63.80 and 61.30% of original grouped cases correctly classified in the Tiv and the Fulani chickens, respectively. The significant values of genetic distance estimated within and between the Tiv and Fulani ecotypes suggests that the populations of the chickens were diverse from one location to another and between the two ecotypes but they were under the influence of similar evolutionary forces.